Strategi Guru Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri TPQ Hidayatullah - Mujab, Mohamad Saeful; Rosadi, Tahrir (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Teacher Strategy in Improving Reading Ability Al-Qur'an Santri TPQ Hidayatullah Klirong, kebumen. The objectives of this research (1) To find out teachers' strategies in improving reading ability Al-Qur’ansantri TPQ Hidayatullah Klirong Kebumen. (2) Knowing the supporting factors and inhibiting factors in the implementation of Teacher strategies in improving reading Al-Qur’ansantri TPQ Hidayatullah Klirong Kebumen.This research is qualitative research with a type of field research, studies in the form of interviews with Head of TPQ, teachers, Santri, Guardian as subjects of interviews, observations of phenomena that occur and documenting the data. Then the data is analyzed using qualitative descriptive methods.The collected data are analyzed using data reduction, data presentation, data collection and conclusion.The results of implementing strategy in improving reading ability Al-Qur'an santri TPQ Hidayatullah santri are able to read the Al-Qur'an in an iterative manner and being able to decipher the tajwid. Santri are also able to follow the imitations with good results. Supporting factors include the implementation of strategy (1) strong commitment between teachers and santri (2) adequate facilities and infrastructure (3) support from guardian. Factors inhibiting the implementation of strategy is teachers who do not implement strategy and santri who act as they please.